KAJIAN KARAKTERISTIK KAWASAN PERMUKIMAN PERKOTAAN Studi Kasus: Permukiman Kampung Wuring, Kecamatan Alok, Kabupaten Sikka - Boer, Alexius (Universitas Atma Jaya Yogyakarta, 2020)
The increase of population is directly proportional to the level of living needs, namely the need for clothing, food, shelter, education, and health. Settlement problems include nonphysical problems between social, economic, cultural, ecological as well as physical environmental problems including housing infrastructure and facilities. The spatial layout of the coastal environment that is irregular and not environmentally will cause various problems. This limited residential environmental condition demands a good change made by the community in the area. The purpose of this research is to examine the spatial layout patterns and conditions of the traditional fishing settlements of the Wuring village in the Wolomarang Village. The results showed that the types of shelter found were permanent, semi-permanent and non-permanent. Wuring settlement partners form a spatial pattern of traditional fishing settlements. Wuring village has complete facilities and inscriptions to support a village but has limitations in facilities and infrastructure. Thus, it is necessary to have a direction in the arrangement of the fishermen settlement of Wuring village, among others, to improve settlement support facilities such as facilities and infrastructure. Conclusion, the spatial pattern of Wuring Village has complete facilities and infrastructure with varied typical residential patterns.